Immunogenicity and safety of quadrivalent and 9-valent human papillomavirus vaccines in Indian clinical trial participants. Issue 6 (30th November 2022) - Garland, Suzanne M.; Anagani, Manjula; Bhatla, Neerja; Chatterjee, Sukanta; Lalwani, Sanjay; Ross, Cecil; Group, Thomas; Lin, Jianxin; Luxembourg, Alain; Walia, Anuj; Tu, Yingmei
ABSTRACT: The quadrivalent human papillomavirus (qHPV; HPV6/11/16/18) and 9-valent HPV (9vHPV; HPV6/11/16/18/31/33/45/52/58) vaccines have demonstrated efficacy, immunogenicity, and safety in international clinical trials. We report outcomes from three completed clinical trials in India: a single-arm study (V501–029 [NCT00380367]) in Indian girls (aged 9–15 years; N  = 110) evaluating qHPV vaccine immunogenicity and safety; a subgroup analysis (n = 225) of Indian girls/boys (9–15 years) and women (16–26 years) from a global study (V503–002 [NCT00943722]) evaluating 9vHPV vaccine immunogenicity and safety; and a qHPV vaccine post-marketing safety surveillance study (V501–125) in Indian females (aged 9–45 years; N  = 188) vaccinated during routine care. In V501–029 and V503–002, HPV vaccines were administered as 3 doses (Day 1, Month 2, Month 6). Serum HPV antibodies were evaluated by competitive Luminex immunoassays at Day 1 and Month 7 (both studies) and Months 12, 24, and 36 (V503–002 only). Adverse events (AEs) were collected by Vaccination Report Card. In V501–125, participants were actively surveilled for serious AEs (SAEs) within 30 days post-qHPV vaccination. In per-protocol analyses, qHPV and 9vHPV vaccines induced robust anti-HPV6/11/16/18 (V501–029) and HPV6/11/16/18/31/33/45/52/58 (V503–002) responses, respectively; ≥97% of participants seroconverted at Month 7 for each vaccine HPV type in both studies, and antibody responses persisted through 36 months in V503–002. The most common AEs were injection-site-associated. Most AEs were mild/moderate; no deaths, vaccine-related SAEs, or discontinuations due to AEs were reported. In V501–125, no SAE was reported. Overall, the qHPV and 9vHPV vaccines elicited robust antibody responses and were generally well tolerated in Indian participants.